Monitoring the interaction of production structures - A. E. Miller; A. M. Davydov (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the development of methodological tools for tracking the parameters of interaction of production structures in the industrial sector of the economy. A system of monitoring the interaction of production structures is proposed, consisting of 3 main stages and including the object, subject, subjects, methods and means of monitoring the process of interaction of production structures. The principles of building an interaction monitoring system are formulated. The developed interaction monitoring system involves the collection and analysis of information about the parameters of interacting production entities selected for observation. Observation as the most important stage of the system of monitoring the interaction of production structures is proposed to be carried out through the use of such methods of collecting information and processing results as analysis of freely available materials, expert survey, questionnaire, statistical accounting, calculation method. The results of the evaluation of the interaction of production structures determined within the framework of the corresponding stage of the monitoring system are studied as fundamental in the implementation of regulatory measures by the interacting structures in terms of specifying regulatory and technical and technological requirements for its participants.